Comparison of Postoperative Occupational Therapy and Narcotic Use in Two Carpometacarpal Arthroplasty Approaches. Issue 2 (27th July 2021) - Sarac, Nikolas; Samade, Richard; Jain, Sonu A.
Abstract : Background: The authors sought to determine whether differences exist in (1) the number of postoperative occupational therapy visits and (2) narcotic use in two carpometacarpal arthroplasty groups. Methods: A retrospective study comparing patients undergoing abductor pollicis longus (APL) suspensionplasty (154 patients) or flexor carpi radialis ligament reconstruction and tendon interposition (FCR LRTI) techniques (40 patients) between January 1, 2012, and August 1, 2018, was performed. Data included demographics, procedure performed, complications, number of postoperative occupational therapy visits, and postoperative morphine equivalent dosage used. Statistical testing used the chi-square test for proportions and the Wilcoxon-Mann-Whitney test for nonnormal data. The significance level was 0.05. Results: The APL suspensionplasty and FCR LRTI groups had similar ages (58.1 ± 7.8 years versus 58.1 ± 7.7 years), sex ratios (73 percent female versus 75 percent female), and preoperative narcotic user proportions (1 percent versus 3 percent). Complication rates following the procedures were similar (21 percent and 18 percent, respectively). The number of postoperative occupational therapy visits following APL suspensionplasty (median, 0; interquartile range, 0 to 4) and FCR LRTI (median, 0; interquartile range, 0 to 4) were not significantly different ( p = 0.961). There was less use of narcotics following APL suspensionplasty (median, 375 morphine equivalent dosage; interquartile range, 241.9 to 525 morphine equivalent dosage) compared with FCR LRTI (median, 462.5 morphine equivalent dosage; interquartile range, 375 to 768.8 morphine equivalent dosage), and this difference was significant ( p = 0.0007). Conclusions: The APL suspensionplasty technique had less narcotic use and similar complication rates and occupational therapy visits compared to FCR LRTI. Prospective studies comparing postoperative pain control and function with these two carpometacarpal arthroplasty techniques may be beneficial. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.